Breast-feeding and complementary feeding practices in the first 6 months of life among Norwegian-Somali and Norwegian-Iraqi infants: the InnBaKost survey. Issue 4 (24th June 2015) - Grewal, Navnit Kaur; Andersen, Lene Frost; Sellen, Daniel; Mosdøl, Annhild; Torheim, Liv Elin
Abstract: Objective: To examine breast-feeding and complementary feeding practices during the first 6 months of life among Norwegian infants of Somali and Iraqi family origin. Design: A cross-sectional survey was performed during March 2013–February 2014. Data were collected using a semi-quantitative FFQ adapted from the second Norwegian national dietary survey among infants in 2006–2007. Setting: Somali-born and Iraqi-born mothers living in eastern Norway were invited to participate. Subjects: One hundred and seven mothers/infants of Somali origin and eighty mothers/infants of Iraqi origin participated. Results: Breast-feeding was almost universally initiated after birth. Only 7 % of Norwegian-Somali and 10 % of Norwegian-Iraqi infants were exclusively breast-fed at 4 months of age. By 1 month of age, water had been introduced to 30 % of Norwegian-Somali and 26 % of Norwegian-Iraqi infants, and infant formula to 44 % and 34 %, respectively. Fifty-four per cent of Norwegian-Somali and 68 % of Norwegian-Iraqi infants had been introduced to solid or semi-solid foods at 4 months of age. Breast-feeding at 6 months of age was more common among Norwegian-Somali infants (79 %) compared with Norwegian-Iraqi infants (58 %; P= 0·001). Multivariate analyses indicated no significant factors associated with exclusive breast-feeding at 3·5 months of age. Factors positively associated with breast-feeding at 6 months were country of origin (Somalia) and parity (>2). Conclusions: Breast-feeding initiation was common among Iraqi-born and Somali-born mothers, but the exclusive breast-feeding period was shorter than recommended in both groups. The study suggests that there is a need for new culture-specific approaches to support exclusive breast-feeding and complementary feeding practices among foreign-born mothers living in Norway.